2020
DOI: 10.3346/jkms.2020.35.e276
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Trends of Suicide Attempt or Non-suicidal Self-injury in Children and Adolescents Visiting Emergency Department

Abstract: Background Non-suicidal self-injury (NSSI) and suicidality are common reasons for child and adolescent psychiatric emergencies. We aimed to investigate the incidence of pediatric emergency department (PED) utilization for psychiatric problems in children and adolescents and to identify demographic and clinical characteristics of youths who visited the PED for suicide attempt (SA) and/or NSSI. Methods The medical records of children and adolescents who visited the PED fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
(71 reference statements)
2
20
0
1
Order By: Relevance
“…Using the KNHDIIS, a national disease statistic, this study analyzed characteristics related to self-harm and suicide attempts in 30046 patients by sex and age, applying weights for the 980 adolescents aged 10-24 years who were hospitalized The emergency room is an important treatment environment for children and adolescents who attempt self-harm and suicide [8,16]. Recently, in Korea and worldwide, the number of visits to the emergency room for self-harm has increased [16]. In particular, it is known that women and older adolescents visit emergency rooms more frequently [4,16], which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the KNHDIIS, a national disease statistic, this study analyzed characteristics related to self-harm and suicide attempts in 30046 patients by sex and age, applying weights for the 980 adolescents aged 10-24 years who were hospitalized The emergency room is an important treatment environment for children and adolescents who attempt self-harm and suicide [8,16]. Recently, in Korea and worldwide, the number of visits to the emergency room for self-harm has increased [16]. In particular, it is known that women and older adolescents visit emergency rooms more frequently [4,16], which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The emergency room is an important treatment environment for children and adolescents who attempt self-harm and suicide [ 8 , 16 ]. Recently, in Korea and worldwide, the number of visits to the emergency room for self-harm has increased [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 70 Temperament is inherited and is usually thought to last a lifetime, but it can also be a marker reflecting the severity of depression, as with high harm avoidance, low self-directedness and cooperativeness. 72 Since severe depression is a risk factor for suicide-related behavior, 73 74 75 the previously reported association between suicide-related behaviors and harm avoidance, self-directedness, and cooperativeness may be attributed to the confounding effect. Self-transcendence may be the TCI dimension that strongly suggests the risk of suicide after the effect of psychiatric symptoms, including mood episodes, is excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that NSSI, suicide, and suicidal behaviors are closely correlated because they are often seen together (11,12,15,46), each increases the risk of the occurrence of the other (47), and due to common genetic (46), phenomenologic features (48) with common risk factors (12). Some researchers have reported that NSSI may be an antecedent of suicide attempts (12), which has led to discussion of a view that the 2 clinical conditions represent the two ends of the same spectrum (11,12,49,50).…”
Section: Discussionmentioning
confidence: 99%